Interaction of light with a non-covalent zinc porphyrin–graphene oxide nanohybrid. Issue 24 (10th June 2020) - Gacka, Ewelina; Burdzinski, Gotard; Marciniak, Bronisław; Kubas, Adam; Lewandowska-Andralojc, Anna
Abstract : Fast electron transfer from the photoexcited ZnTPPH singlet state to GO sheets was detected by ultrafast time-resolved transient absorption spectroscopy. Abstract : The present study explores the influence of graphene oxide (GO) on deactivation pathways of the excited states of zinc 5, 10, 15, 20-tetrakis(4-(hydroxyphenyl))porphyrin (ZnTPPH). The interaction of light with free ZnTPPH molecules and with ZnTPPH molecules adsorbed on graphene oxide sheets was probed via UV-vis spectroscopy, fluorescence spectroscopy, femtosecond pump–probe technique and nanosecond flash photolysis. Formation of the ground-state ZnTPPH–GO complex in solution was monitored by the red-shift of the porphyrin Soret absorption band. It was found that Stern–Volmer fluorescence quenching can be described in terms of two different quenching regimes depending on the GO concentration. In addition, our comprehensive analysis of the steady-state and time-resolved emission experiments led to the conclusion that the observed quenching was entirely attributable to a static mechanism. Laser flash photolysis showed that the triplet lifetime of the ZnTPPH increased in the presence of GO from 174 μs to 292 μs, which is related to the decrease in the rate constant of a radiationless decay mechanism involving rotation of the peripheral hydroxyphenyl rings of the porphyrin. Femtosecond transient absorption spectroscopy demonstrated the presence of a fast photoinduced electron transfer from the singlet excited state of ZnTPPH to the GO sheets, as indicated by the formation of a porphyrin radical cation. Quantum chemical calculations were used to gain deeper insights into the nature of the electronically excited states in the free ZnTPPH as well as in the ZnTPPH–GO complex.